Synoptic timescale linkage between midlatitude winter troughs Sahara temperature patterns and northern Congo rainfall: A building block of regional climate variability. (15th February 2021) - Ward, Neil; Fink, Andreas H.; Keane, Richard J.; Guichard, Françoise; Marsham, John H.; Parker, Douglas J.; Taylor, Christopher M.
Abstract: A coherent synoptic sequence, mostly over North Africa, is identified whereby an upper‐level midlatitude trough (in November–March) excites several days of quasi‐stationary near‐surface warming across the Sahara, leading to rainfall events over northern Congo (NC), and perturbed weather more widely. Ahead of NC rainfall events, composite sequences first identify troughs for several days near Iberia, followed by relatively quick transfer to the Central Mediterranean (CMed). Iberia and CMed daily trough‐strength indices reveal that both lead to warming and NC rainfall. Iberia trough linkages develop through West Africa and take longer to reach NC, while CMed linkages reach NC faster (2–3 days), with impact extent focused mostly south and east of CMed. Building up to the rainfall events, initial warming over the central Sahara migrates southeastward close to NC, ultimately with typical magnitude of about 1–2°C at 10–15°N. Such anomalies are statistically predictive for NC daily rainfall and associated nearby atmospheric features: anomalous low‐level southerly wind and increased moisture; anomalous low‐level westerly wind and vertical easterly shear to 600 hPa; increased mid‐level moisture (600 hPa), which along with low‐level moisture, connects northward into midlatitudes. A secondary route identified by which Iberia troughs can impact NC rainfall is through direct atmospheric teleconnection with precipitation to the west of NC, and subsequent migration of that convection eastward into NC. The eastern side of NC generally shows a small lag on western parts, and links more strongly to CMed troughs. Taken together, the lagged synoptic expression of Iberia and CMed troughs is widespread over several days, including much of North Africa (to equatorial latitudes), southwestern Asia, eastern Africa and the western Indian Ocean. Overall, these results can contribute to situational awareness for weather forecasters across the zones influenced by the troughs, while also providing a framework for climate timescale analyses. Abstract : Sequence associated with strong Iberia troughs (December–March): negative 200‐hPa geopotential height anomalies (Z200) at Day 0 (dotted black); positive 850‐hPa temperature anomalies (T850) at Day +2 (solid red) and Day +6 (dashed red); negative outgoing longwave radiation anomalies (OLR, indicative of enhanced tropical rainfall/convection) at Day +2 (solid green) and Day +6 (dashed green); positive 850‐hPa specific humidity anomalies (Q850) at Day +6 (dashed blue). Black vectors depict low‐level wind anomaly at Day +6 (not to scale).